Pendekatan Sosiologi Pengetahuan Kiri Islam Hasan HanafÃ® - Hanif, Abdulloh (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
The Islamic Left was not born out of a vacuum. It is a manifestation of a particular social constructs. The Islamic Left is Hasan HanafÃ®âs thought which is based on his experiences. As to view the Islamic Left as a social reality, sociology of knowledge will be used. The sociology of knowledge not only rejects the notion that social reality is born from a vacuum, but it also analyzes the socially constructed reality, and how the reality was accepted by society as a fact. Therefore, the sociology of knowledge will analyze process of the formation of the Islamic Left as a social reality, and how the Islamic Left can be seen and accepted by society. In an objective reality, the Islamic Left is a discourse of thought of a particular experience with the aim of revolution. While in a subjective reality, the Islamic Left can be considered as an individual who was born at a time when human values are at stake in the history of life, either in a global context or in a context of Islam itself. Thus, it builds awareness that distinguishes him/herself psychologically with others. This study expects the ideas contained in the Islamic Left to be used widely to analyze different contexts so that the application of the Islamic Left ideas can be viewed.